Developing a comprehensive performance measurement system for waqf institutions - Noordin, Nazrul Hazizi; Haron, Siti Nurah; Kassim, Salina (Emerald Publishers, 2017)
Purpose The purpose of this paper is to contribute to the literature on management of waqf institutions by developing a contingency framework and outlining approaches that can be followed to instigate a comprehensive performance measurement system (PMS).